2012
DOI: 10.1890/11-1102.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem assembly rules: the interplay of green and brown webs during salt marsh succession

Abstract: Abstract. Current theories about vegetation succession and food web assembly are poorly compatible, as food webs are generally viewed to be static, and succession is usually analyzed without the inclusion of higher trophic levels. In this study we present results from a detailed analysis of ecosystem assembly rules over a chronosequence of 100 years of salt marsh succession. First, using 13 yearlong observations on vegetation and soil parameters in different successional stages, we show that the space-for-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 71 publications
(96 reference statements)
6
110
0
4
Order By: Relevance
“…Our main results fit well to the assembly rule found by Schrama et al (2012) in an European salt-marsh, through a chronosequence of 100 years. They indeed described that, at the beginning of the succession, most incoming fluxes of organic matter and decomposers are mostly marine, whereas the importance of terrestrial matter and invertebrates increases over time.…”
Section: Discussionsupporting
confidence: 88%
“…Our main results fit well to the assembly rule found by Schrama et al (2012) in an European salt-marsh, through a chronosequence of 100 years. They indeed described that, at the beginning of the succession, most incoming fluxes of organic matter and decomposers are mostly marine, whereas the importance of terrestrial matter and invertebrates increases over time.…”
Section: Discussionsupporting
confidence: 88%
“…This stage has previously been shown to have a peak in plant diversity (Schrama et al, 2012). The extent of mycorrhizal colonization of the plants occurring at the study sites was not explored.…”
Section: Discussionmentioning
confidence: 99%
“…The study site presents a well-documented salt marsh chronosequence that has been calibrated using topographic maps, aerial photographs and monitoring permanent plots at different successional stages for over 20 years (Olff et al, 1997;Schrama et al, 2012). For this study, five successional stages were identified and estimated as 0, 5, 35, 65 and 105 years of succession (hereafter referred as 'Stage' followed by the corresponding year) in May 2012 (Supplementary Figure S1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations